The Cultural Life of Machine Learning An Incursion into Critical AI Studies - Roberge, Jonathan; Castelle, Michael (Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
XV, 289 p. 10 illus., 7 illus. in color.